The hernandez and fernandez genes of Drosophila specify eye and antenna. - Suzanne, M.; Estella, C.; Calleja, M.; Sanchez-Herrero, E. (Developmental Biology, 2003)
The formation of different structures in Drosophila depends on the combined activities of selector genes and signaling pathways. For instance, the antenna requires the selector gene homothorax, which distinguishes between the leg and the antenna and can specify distal antenna if expressed ectopically. Similarly, the eye is formed by a group of "eye-specifying" genes, among them eyeless, which can direct eye development ectopically. We report here the characterization of the hernandez and fernandez genes, expressed in the antennal and eye primordia of the eye-antenna imaginal disc. The predicted proteins encoded by these two genes have 27% common amino acids and include a Pipsqueak domain. Reduced expression of either hernandez or fernandez mildly affects antenna and eye development, while the inactivation of both genes partially transforms distal antenna into leg. Ectopic expression of either of the two genes results in two different phenotypes: it can form distal antenna, activating genes like homothorax, spineless, and spalt, and it can promote eye development and activates eyeless. Reciprocally, eyeless can induce hernandez and fernandez expression, and homothorax and spineless can activate both hernandez and fernandez when ectopically expressed. The formation of eye by these genes seems to require Notch signaling, since the induction of ectopic eyes and the activation of eyeless by the hernandez gene are suppressed when the Notch function is compromised. Our results show that the hernandez and fernandez genes are required for antennal and eye development and are also able to specify eye or antenna ectopically.